2017
DOI: 10.1186/s40360-017-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous formulation of delayed-release omeprazole capsules: alert for importing countries

Abstract: BackgroundPoor drug quality is a matter of serious concern, especially in countries where drug regulation and law enforcement are constrained by limited resources. This study was carried out to investigate the cause of quality failure of omeprazole in Cambodia in 2010 and Myanmar in 2014.MethodsWe conducted pharmacopoeial quantity, content uniformity and dissolution tests of 156 samples of omeprazole capsules collected in Cambodia in 2010 and Myanmar in 2014. High failure rates were found, especially in dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…In Cambodia 2010, a study conducted by Yoshida et al [14] found serious quality deficiencies, especially in the dissolution test, in omeprazole samples from some manufacturers. Similar results were reported from Myanmar in 2014 by Rahman et al [15]. Interestingly, manufacturers of those poor-quality products had also produced some of the samples obtained in our current study.…”
Section: Quality Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…In Cambodia 2010, a study conducted by Yoshida et al [14] found serious quality deficiencies, especially in the dissolution test, in omeprazole samples from some manufacturers. Similar results were reported from Myanmar in 2014 by Rahman et al [15]. Interestingly, manufacturers of those poor-quality products had also produced some of the samples obtained in our current study.…”
Section: Quality Analysissupporting
confidence: 92%
“…Similar results were reported from Myanmar in 2014 by Rahman et al . . Interestingly, manufacturers of those poor‐quality products had also produced some of the samples obtained in our current study.…”
Section: Methodsmentioning
confidence: 75%
“…In the DS assessment of MF, 1 MF-IR sample out of 49 samples (2.0%) and 9 MF-ER samples out of 13 samples (69.2%) were pending. All the medicines contained an acceptable amount of active ingredient, so the tablets could harden and change in terms of other properties, even though the content may not be lost due, for example, to heat [21,22], since extended release tablets and sustained-release tablets require special technology that may not be readily available to manufacturers in developing countries [23]. Quality-test-failing MF-ER samples were manufactured by one manufacturer out of four.…”
Section: Quality Analysismentioning
confidence: 99%
“…It is widely used for the treatment of gastric and duodenal diseases [16,17], and it also has a good therapeutic effect on most ARDs [11]. OMZ is very poorly soluble [18], but it has high permeability and is highly absorbable (> 90%) in the intestinal tract. It belongs to the biopharmaceutics classification system (BCS) class II [19] and the dissolution rate is a key factor for that ensures a better release.…”
Section: Fourier Transform-infrared Spectroscopy (Ftir)mentioning
confidence: 99%
“…The appearance of the capsules is shown in Figure 4a. The capsules we developed were prepared by mixing and filling 170 mg of OMZ-CD, 250 mg of NaHCO 3, and 400 uble [18]; the saturation solubility of OMZ in water and PBS (pH 6.8) were 75.38 ± 1.52 μg/mL and 80.26 ± 1.50 μg/mL (see Figure 2a). In an attempt to minimize these drawbacks, the aim of this work was to evaluate the capability of OMZ for the oral delivery of drug when associated to CD.…”
Section: Physical Characteristics Of Capsulesmentioning
confidence: 99%